PERTUMBUHAN STEK HORIZONTAL BATANG JARAK PAGAR (Jatropha curcas L.) YANG DIINTRODUKSI DENGAN PSEUDOMONAD FLUORESEN - Linda Advinda (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2018)
Jatropha curcas L. is one of the plants that can be developed as raw material of biodiesel. One of the efforts to increase the production of J. curcas is the propagation of stem cuttings horizontally. Efforts to stimulate root growth can be accomplished by adding Plant Growth Regulators (PGRs). PGRs can be obtained naturally or synthetically. Indole acetic acid (IAA) is one of PGRs, which is not only produced by plants but can also be produced by rhizobacteria. One such rhizobacteria is fluorescent pseudomonad. The objectives of the study were to know the response of growth of horizontal stem cuttings after being introduced with fluorescent pseudomonad. This research is an experimental research. Complete Randomized Design with 6 treatments and 4 replications. The treatments were soaking of J. curcas stem cuttings with fluorescent pseudomonad isolate suspension PfPj3 suspension concentration of 0% (without suspension), 5%, 10%, 15%, 20%, and 25%. Observation of the research is the beginning of the shoots, the number of shoots, and the length of the J. curcas stem shoot. The data obtained were analyzed using Anova and DNMRT significant level of 5%. The results showed that horizontal stem cuttings of J. curcas with fluorescent pseudomonad suspension influenced early shoot, shoot number, and shoot length. A 10% fluorescent pseudomonad concentration can cause shoots to appear early, while a concentration of 20% causes the largest number of shoots.